Study on application modes of military Internet of Things (MIOT) - Lan Yushi; Jiang Fei; Yu Hui (2012 IEEE International Conference on Computer Science and Automation Engineering, 2012)
Recently, the Internet of Things (IOT) has obtained rapid development and has a significant impact on the military field. This paper first proposes a conception of military internet of things (MIOT) and analyzes the architecture of MIOT in detail. Then, three modes of MIOT, i.e., information sensing, information transmission and information serving, are respectively studied to show various military domain applications. Finally, an application assumption of MIOT from the weapon control aspect is given to validate the proposed application modes.